Distribution and Transmission of Colistin Resistance Genes mcr-1 and mcr-3 among Nontyphoidal Salmonella Isolates in China from 2011 to 2020 - Tingting Yang; Weiwei Li; Qingpo Cui; Xiaoxia Qin; Bosheng Li; Xiugui Li; Huayun Jia; Xiaorong Yang; Chengwei Liu; Yang Wang; Shaolin Wang; Jianzhong Shen; et al. (Microbiology Spectrum, 2023)
ABSTRACT Mobile colistin resistance (mcr) genes are present mainly in plasmids and can disseminate clonally or horizontally via either plasmids or insertion sequences in different genomic locations among the Enterobacteriaceae. A nationwide large-scale study on mcr prevalence and transmission in nontyphoidal Salmonella isolates is still lacking. Here, we identified 140 mcr-positive Salmonella isolates out of 7,106 isolates from 29 provinces in China from 2011 to 2020. We aligned short reads to putative plasmids from long-read hybrid assemblies and predicted the plasmid backbones of non-long-read sequencing isolates to elucidate mcr transmission patterns. The mcr-1 and mcr-3 genes are transmitted on similar high-risk clones (sequence type 34 [ST34]) but through plasmids of various replicon types. Furthermore, the ban on colistin use in food animals can lead to a decrease in the mcr-positive Salmonella prevalence among diarrheal patients, related mainly to IncHI2A_IncHI2 plasmids. We provide a framework for plasmid data incorporation into genomic surveillance systems, contributing to a better understanding of mcr spread and transmission. IMPORTANCE Nontyphoidal Salmonella is one of four major causative agents of diarrheal diseases globally, with most cases of salmonellosis being mild. Antimicrobial treatments are required for cases of life-threatening infections, and colistin is one of the last-line antibiotics for the treatment of multidrug-resistant Salmonella infections. However, the efficacy of colistin has been compromised by the emergence of various mcr genes. To elucidate the transmission of mcr genes in Salmonella isolates, our study analyzed 7,106 Salmonella strains from 29 provinces in China from 2011 to 2020. The results showed that mcr genes are transmitted on similar high-risk clones (ST34) but through plasmids of various replicon types. In addition, our data illustrated that the ban on the use of colistin in food animals led to a significant decrease in mcr-positive isolates. Our findings offer an essential step toward a more comprehensive understanding of the spread and transmission of mcr genes.